The Dance of Change : The Challenges of Sustaining Momentum in Learning Organizations (A Fifth Discipline Resource) - Senge, P., Kleiner, A., Roberts, C., Ross, R.. (London, Boston Nicholas Brealey Publishing, 2007)
The Dance of Change offers exercises, tools and techniques for sustaining organisational learning over the long term, as well as suggestions, advice, cautions and warnings based on the experience of people who have already followed the path suggested by the author in The Fifth Discipline. The central message of the text is that learning is the only sustainable competitive advantage.
Keywords: Management